1981
DOI: 10.1007/bf02626775
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of anorectal pressures in Hirschsprung's disease

Abstract: Anorectal motility was investigated in 146 children with Hirschsprung's disease and 89 normal control subjects. Pressures were recorded in the rectum and anal canal at rest and during rectal distention. The rectoanal inhibitory reflex was absent in all but four patients. Intraluminal rectal pressure was higher than normal (16.5 vs. 14.6 cm H2O, P less than 0.03), with more frequent (41 per cent vs. 18 per cent, P less than 0.01) pressure waves. In the upper anal canal, there were more frequent (62 per cent vs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…We found that USWs were rare in Hirschsprung disease, and there were significant differences in the anal pressure and frequency of anal slow waves between patients with USWs and those with Hirschsprung disease. Our data on the low frequency of anal slow waves in Hirschsprung disease were compatible with the data reported by Faverdin et al [13]. Another clinical entity to be discussed is bultrashort Hirschsprung diseaseQ or internal anal sphincter achalasia [14].…”
Section: Discussionsupporting
confidence: 86%
“…We found that USWs were rare in Hirschsprung disease, and there were significant differences in the anal pressure and frequency of anal slow waves between patients with USWs and those with Hirschsprung disease. Our data on the low frequency of anal slow waves in Hirschsprung disease were compatible with the data reported by Faverdin et al [13]. Another clinical entity to be discussed is bultrashort Hirschsprung diseaseQ or internal anal sphincter achalasia [14].…”
Section: Discussionsupporting
confidence: 86%
“…The frequency of SW differed between patients and control subjects. The median (range) frequency was 9 (0-12) per minute in patients and 12 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) in controls (p<0.001). Overall, 22 patients (44%) were outside the 5 th -95 th percentile of controls in at least one of these sphincter function parameters.…”
Section: Resultsmentioning
confidence: 91%
“…For example, absence of the recto-anal inhibitory reflex (RAIR) suggests Hirschsprung's disease [9]. Other anorectal pressure abnormalities have been described.…”
Section: Introductionmentioning
confidence: 98%
“…Patients usually have increased anorectal resting pressure (ARP) and do not possess rectoanal inhibitory reflex on manometry [3]. The spastic contraction in the aganglionic segment can be attributed either to the lack of smooth muscle relaxants, including nitric oxide, vasoactive intestinal peptide, and carbon monoxide from nonadrenergic, noncholinergic neurons [4][5][6], or to the excessive activity of excitatory acetylcholine and substance P released from hypertrophic nerves [7,8].…”
mentioning
confidence: 99%
“…Hirschsprung disease is characterized by aganglionosis in both the submucosal and myenteric plexuses secondary to the absence of the enteric nervous system, with concurrent hypertrophic nerve trunks thought to mainly originate from extrinsic, parasympathetic nerves [1,2]. Patients usually have increased anorectal resting pressure (ARP) and do not possess rectoanal inhibitory reflex on manometry [3]. The spastic contraction in the aganglionic segment can be attributed either to the lack of smooth muscle relaxants, including nitric oxide, vasoactive intestinal peptide, and carbon monoxide from nonadrenergic, noncholinergic neurons [4-6], or to the excessive activity of excitatory acetylcholine and substance P released from hypertrophic nerves [7,8].…”
mentioning
confidence: 99%